Spatial Patterns of Taxonomic, Functional, and Phylogenetic Diversity of Mammals in Southern Mexico - Cintia Natalia Martín‐Regalado; Mario C. Lavariega; Miguel Briones‐Salas (Ecology and Evolution)
ABSTRACT Biodiversity is multidimensional and should therefore be characterized using multiple approaches to understand the patterns at various temporal and spatial scales. Taxonomic, functional, and phylogenetic measurements of diversity are now recognized as comprehensive methods for understanding the relationships among species diversity, associated ecological processes, and the evolutionary history of species within communities. However, spatial incongruence among these different dimensions of diversity has been found to be common at global and regional levels, posing challenges for conservation. By using species distribution models built with correlative method, we investigated whether downscaling spatial analyses of multidimensional diversity across mammal groups (flying mammals, small‐sized mammals, and medium and large‐sized mammals) maintain mismatch patterns in a megadiverse mammal unit (Oaxaca state, southern Mexico) at three spatial resolutions and how well diversity hotspots are protected. We found similar spatial patterns and high correlations across the analyzed resolutions, suggesting interchangeability. As expected, we observed incongruence in spatial patterns among multidimensional biodiversity measurements (average of 68.7%). Species richness partially matched the global pattern, as topographic heterogeneity facilitated refugia and speciation in mountains, while productivity in lowlands supported a high number of species. As observed globally, functional diversity was higher in temperate areas; however, redundancy was not found in tropical ecosystems but rather in semiarid ones, suggesting that environmental filtering plays an important role in structuring communities. Contrary to expectations, phylogenetic diversity increased in tropical ecosystems, where dispersal events allow species to accumulate through invasion processes. Among mammal groups, we also found disparate patterns, suggesting differences in dispersal potential and energy demand. Protected area systems overlapped very little with the proposed multidimensional conservation areas, with a higher overlap found in social initiatives than in governmental ones. Our findings support the notion that there is spatial incongruence between the dimensions of biodiversity, which has implications for subregional mammal conservation.